The Role of Government in MSMEs:The Empowerment of MSMEs During the Free Trade Era in Indonesia - Dhian Kusumawardhani; Amy Y. Rahayu; Irfan Ridwan Maksum (Australasian Accounting, Business and Finance Journal, 2015)
As the era of globalisation has progressed, the free-trade paradigm – in which the role of government in every aspect of economic development is minimised, replaced by the power of the free market – has inevitably spread across countries throughout the world. Despite the positive outcomes that can be obtained from the idea of free liberalisation in achieving economic growth and opportunities, this paper will propose that governments must continue to have a strong role in their countries’ economies, particularly in developing countries such as Indonesia. This argument is justified on the basis of the threat that free trade poses to some informal sectors called micro and small and medium enterprises (MSMEs), which have commonly shown low levels of competitiveness in the global market. Thus their very survival heavily depends on government involvement. The Indonesian government has launched many policies to help SMEs become and remain more competitive; for example, the Technology for Regions Program (Iptekda), which combines state support and a market-based approach for MSMEs’ empowerment. This paper conducts a case study of the Iptekda program for the empowerment of MSMEs in Malang Raya. The research will address two issues: why government intervention is still required for MSE capacity-building; and how the program may help MSMEs improve their capacity and competitiveness. To answer these questions, this paper will apply a qualitative approach that uses in-depth interview with the owners of five MSMEs. The results reveal that MSMEs benefit from the program in terms of improved productivity, marketing and insights into MSMEs as an economic sector. The research limitation is that it consists solely of qualitative findings; the findings need to be combined with quantitative data for more-reliable results. Replication of this study using larger samples and a broader geographic base is suggested for promoting programs to empower MSMEs in Indonesia.
Keywords: Role of Government; MSE; Indonesia; Free Trade Era